CFD analysis of forced convective heat transfer coefficients at windward building facades: Influence of building geometry. Issue 146 (November 2015) - Montazeri, H.; Blocken, B.; Derome, D.; Carmeliet, J.; Hensen, J.L.M.
Abstract: Knowledge of the convective heat transfer coefficient (CHTC) for external building surfaces is essential for analysis of building heat gains and losses and hygrothermal analysis of building components. The CHTC is influenced by a wide range of parameters. Previous studies analysed the influence of position on the building facade, roughness, wind speed, wind direction, local airflow pattern and surface-to-air temperature differences. Among methods, Computational Fluid Dynamics (CFD) is a useful tool to determine the distribution of the CHTC across building facades as a function of the governing parameters . However, to the best of our knowledge, research on the influence of building size and geometry on the CHTC is very limited . Therefore this paper presents high-resolution 3D steady Reynolds-averaged Navier-Stokes (RANS) CFD simulations of forced convective heat transfer at the windward facade of 22 buildings of different geometry. First, a CFD validation study focused on CHTC is performed based on wind-tunnel measurements of surface temperature for a reduced-scale wall-mounted cubic obstacle. Next, the influence of building geometry on the CHTC distribution is investigated at different reference wind speeds, U 10, for three groups: buildings with H ≥ W, buildings with H ≤ W and buildings with H = W . The results show that CHTC / ( U 10 0.84 ) is relatively insensitive to the reference wind speed. For W =10 m and by increasing H from 10 m to 80 m, the surface-averaged CHTC / ( U 10 0.84 ) on the windward facade increases by about 20%. However, for H =10 m, increasing the building width from 10 to 80 m has the opposite impact on the surface-averaged CHTC / ( U 10 0.84 ), which decreases by more than 33%. For buildings with H = W, it decreases by more than 10% as H and W increase from 10 to 40 m, and remains approximately constant for higher values of H (= W ). The reason for these trends are explained. Graphical abstract: Highlights: Influence of building geometry on exterior convective heat transfer coefficients (CHTC). A detailed validation study: steady RANS indicates satisfactory agreement with experiments for windward surface. Surface-averaged CHTC ( U 10 0.84 ) is relatively insensitive to reference wind speed, U 10 . For a constant value of width, by increasing height of building surface-averaged CHTC increases. For a constant value of height, by increasing width of building surface-averaged CHTC decreases.